2013
DOI: 10.1007/s00403-013-1330-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased HMGB1 serum levels and altered HMGB1 expression in patients with psoriasis vulgaris

Abstract: High mobility group box-1 (HMGB1) has been implicated as a pro-inflammatory cytokine in the pathogenesis of various inflammatory and autoimmune diseases. However, information about HMGB1 in inflammatory skin diseases is unknown. Herein, we investigated the serum HMGB1 levels and tissue HMGB1 expression in patients with psoriasis vulgaris (PV) and atopic dermatitis (AD). Serum levels of HMGB1 in patients with PV and AD were detected by enzyme-linked immunosorbent assay (ELISA). The expression of HMGB1 in lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 15 publications
7
44
1
Order By: Relevance
“…HMGB1 is secreted actively by immune cells such as monocytes, macrophages, and dendritic cells [6]. A previous study suggested that the cytoplasmic HMGB1 existed in lesional skin of lupus erythematosus, psoriasis vulgaris and AD [26,27]. In our study, we also found that HMGB1 expression was up regulated in AD mice and treatment with resveratrol attenuated this process (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…HMGB1 is secreted actively by immune cells such as monocytes, macrophages, and dendritic cells [6]. A previous study suggested that the cytoplasmic HMGB1 existed in lesional skin of lupus erythematosus, psoriasis vulgaris and AD [26,27]. In our study, we also found that HMGB1 expression was up regulated in AD mice and treatment with resveratrol attenuated this process (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous work first investigated the involvement of HMGB1 with PV, and demonstrated the altered HMGB1 distribution in the epidermis and enhanced HMGB1 serum levels of PV patients . In this study, abundant expression of HMGB1 was also detected in cytoplasm of IMQ‐induced psoriatic skin lesions.…”
Section: Discussionsupporting
confidence: 51%
“…To investigate whether HMGB1 acts in other roles in the pathogenic mechanism of psoriasis, some preliminary studies have been carried out. Our published work demonstrated that the serum HMGB1 levels were markedly elevated in patients with psoriasis vulgaris (PV) and significantly reduced after glycyrrhizin treatment . We also indicated that HMGB1 was abundantly expressed in the cytoplasm of the epidermis of PV patients .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, T‐helper (Th)‐1, Th‐17 and Th‐22 cell populations are expanded and stimulated to release inflammatory cytokines, including tumour necrosis factor‐a (TNF‐a), interleukin (IL)‐17 and IL‐22 . Increased production of these cytokines, chemokines and growth factors has been found to be present within the skin as well as in the circulation in psoriasis patients …”
Section: Introductionmentioning
confidence: 99%